Digital Trust Management: Strategies for Building Organizational Trust in the Age of Artificial Intelligence - Yunior Pasagi; Prastiyo Diatmono (PT. Anagata Sembagi Education, 2026)
Digital trust is a strategic foundation for organizations adopting artificial intelligence (AI) in decision-making, public services, and stakeholder interactions. The increasing use of AI raises concerns regarding algorithm transparency, accountability, data privacy, and the risk of bias, thus eroding organizational trust in AI systems and external trust in organizations if not systematically managed. This article aims to analyze digital trust management strategies for building organizational trust in the AI era through a systematic literature review based on the PRISMA framework. Searches were conducted in Scopus, Web of Science, and Google Scholar databases with additional independent searches, resulting in 33 articles meeting the inclusion criteria out of a total of 148 identified articles. The study results indicate that organizational trust in AI is shaped by five main pillars: algorithmic transparency and explainable AI, governance and regulatory compliance, technical competence and system reliability, the human dimension and employee psychological contracts, and digital trust infrastructure such as zero trust architecture and IoT reputation. This study offers a novel Digital Trust Management (DTM) framework that integrates technology, governance, and human dimensions across sectors, differing from previous studies that tended to be partial and sectoral. These findings offer practical implications for organizations in designing sustainable AI adoption strategies that are trusted by all stakeholders..